CP-ABE based data access control for cloud storage - SUN Guo-zi1; DONG Yu1; LI Yun1 (Tongxin xuebao, 2011)
To solve the safety issues in cloud storage services for network characteristics and data sharing characteristics,and based on the CP-ABE（cipertext policy-attribute based encryption） algorithm,a cipher text access control mechanism was proposed.According to access control and related architecture,the corresponding secure data structure algorithms were given.After this,the simulations and the performance analysis were given to evaluate our algorithm.Under the premise of untrusted service provider,the proposed mechanism can ensure the data security of the cloud storage system in an open environment,and can reduce right management complexity through property management.